Isolation and characterization of antioxidant compounds from Combretum apiculatum (Sond.) subsp apiculatum leaf extracts - Aderogba, M.A. (Mutalib) (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.